Marketing Communication Strategy of Anti Acid Fertilizer CV. Sobat Tani at the Farmer Group Level in increasing Sales in Penajam Paser Utara Regency - Nasrullah; Andi Vita Sukmarini; Mujahid (Universitas Muhammadiyah Palu, 2024)
Anti Acid Fertilizer CV. Sobat Tani is a new product in solving soil acidity problems for agricultural land so it needs extra work in delivering products to farmers, so it needs a communication strategy by CV. Sobat Tani in marketing anti-acid fertilizer at the Farmer Group Level in Penajam Paser Utara Regency. This study aims to determine the marketing communication strategy of anti-acid fertilizer by CV. Farmer Friends at the Farmer Group Level in increasing sales in Penajam Paser Utara Regency as well as supporting and inhibiting factors in the implementation of the marketing communication strategy. This research uses qualitative methods to explore information by interviews and field observations from certain informants. The results of this study show that 1) Marketing communication strategy of anti-acid fertilizer CV. Sobat Tani at the farmer group level in increasing sales in Penajam Paser Utara Regency are events and experiences, direct marketing, word of mouth marketing and personal sales. (2) Supporting factors for marketing communication strategy of anti-acid fertilizer CV. Farmer friends at the farmer group level in increasing sales in Penajam Paser Utara Regency are consumer readiness to buy, the existence of competitors and media preferences and availability. But the main one is to get the support of the local government of Penajam Paser Utara Regency. (3) Inhibiting factors of marketing communication strategy of anti-acid fertilizer CV. Sobat Tani at the farmer group level in increasing sales in Penajam Paser Utara Regency is budget availability, limited advertising and sales promotion, limited personal selling resources and public relations at CV. Sobat Tani.